Characterization of the thorium-229 defect structure in CaF2 crystals - S Takatori; M Pimon; S Pollitt; M Bartokos; K Beeks; A Grüneis; T Hiraki; T Honma; N Hosseini; A Leitner; T Masuda; I Morawetz; et al. (New Journal of Physics)
Recent advancements in laser excitation of the low-energy thorium-229 ( ^229 Th) nuclear isomeric state in calcium fluoride (CaF _2 ) single crystals render this system a promising candidate for a solid-state nuclear clock. Nonetheless, the precise experimental determination of the microscopic ion configuration surrounding the doped ^229 Th and its electronic charge state remains a critical challenge. Such characterization is essential for precisely controlling the clock transition and evaluating the performance of this solid-state nuclear clock system. In this study, we use x-ray absorption fine structure spectroscopy of ^229 Th:CaF _2 to investigate the charge state and coordination environment of doped ^229 Th. The results indicate that ^229 Th displays a 4+ oxidation state at the substitutional site of a Ca ^2+ ion, with charge compensated provided by two F ^− ions positioned at interstitial sites adjacent to ^229 Th.